Reassessing attachment theory in child welfare - White, Sue 1961-; Gibson, Matthew; Wastell, David ca. 20./21. Jh; Walsh, Patricia 1944- (Policy Press, 2020)
This book offers an analysis and summary of the uses, abuses and limitations of attachment theory in contemporary child welfare practice. Analysing the primary science and drawing on the authors' original empirical work, the book shows how attachment theory can distort and influence decision-making. It argues that the dominant view of attachment theory may promote a problematic diagnostic mindset, whilst undervaluing the enduring relationships between children and adults. The book concludes that attachment theory can still play an important role in child welfare practice, but the balance of the research agenda needs a radical shift towards a sophisticated understanding of the realities of human experience to inform ethical practice
Title from publisher's bibliographic system (viewed on 04 Mar 2021)
Keywords: Child welfare / Great Britain; Social service / Great Britain